Enhancing composition control of alloy nanoparticles from gas aggregation source by in operando optical emission spectroscopy. Issue 3 (23rd December 2020) - Drewes, Jonas; Vahl, Alexander; Carstens, Niko; Strunskus, Thomas; Polonskyi, Oleksandr; Faupel, Franz
Abstract: The use of multicomponent targets allows the gas‐phase synthesis of a large variety of alloy nanoparticles (NPs) via gas aggregation sources. However, the redeposition of sputtered material impacts the composition of alloy NPs, as demonstrated here for the case of AgAu alloy NPs. To enable NPs with tailored Au fractions, in operando control over the composition of the NPs is in high demand. We suggest the use of optical emission spectroscopy as a versatile diagnostic tool to determine and control the composition of the NPs. A strong correlation between operating pressure, intensity ratio of Ag and Au emission lines, and the obtained NP compositions is observed. This allows precise in operando control of alloy NP composition obtained from multicomponent targets. Abstract : The multicomponent target approach is applied to synthesize AgAu nanoparticles with an adjustable composition via a gas aggregation source. The effect of redeposition is investigated in detail, with the composition of nanoparticles being strongly affected. A novel combination of a gas aggregation source and in operando optical emission spectroscopy is presented as a tool for enhancing composition control of alloy nanoparticles.